Dinâmica do fósforo de sedimentos oriundos de bacia hidrográfica subtropical compoluição rural e urbana - Zafar, Mohsin (2015)
Areas at steep slopes in the catchments with high occupation by family farmers in Southern Brazil, even with a high surface covered with regenerated forests, are characterized by the persistence of sources of rural and urban pollution that are undermining the quality of aquatic systems. The unfair use of soil outside its capability, the adoption of inadequate soil tillage systems, the integrated system of animal production (poultry and swine) in quantities environmentally intolerable and the untreated domestic sewage from small villages are the main factors responsible for the input of high amounts of phosphorus into watercourses. In this context, the present doctoral thesis aims (i) monitoring the temporal variation in sediment-bound phosphorus in sub-catchments under different land-use and soil tillage systems and (ii) assessment of the potential of sediments from rural and urban sources to behave as source or sink of phosphorus for aquatic systems. In the Guaporé River catchment, six representative headwater sub-catchments with contrasting land-use and soil management were monitored. The selected sub-catchments were characterized by: (i) predominance of native forest (control); (ii) predominance of areas transformed to agriculture recently, but under conventional tillage CT (sub1); (iii) areas under CT, but with predominance of Ilex plantations (sub2); (iv) predominance of tobacco cultivation of long term under CT (sub3); (v) intensive agriculture under no-tillage NT (sub4); and (vi) intensive agriculture under NT and receiving untreated sewage of a twenty thousand inhabitant town (sub5). In addition, five points of the main river (P1 to P5) were monitored: the first one is located near to the junction of the sub-catchments 4 and 5, and the last one at the outlet of the watershed. Suspended and bed sediments were collected, comprising ten field campaigns performed in the monitoring period of 24 months (October 2012 to October 2014). The different fractions of phosphorus (P) of sediment were analyzed considering the bioavailability. The P sorption-desorption parameters in the sediments were estimated. The conversion of native forest for annual crops production areas promotes the production of sediments with higher amounts of total, inorganic and labile phosphorus. The values of maxima phosphorus adsorption capacity, instantaneous available and potentially available phosphorus forms, desorption rate and mobility index of phosphorus in sediments collected in the different sub-catchments in the following order: native forest < CT < CT with the intensive production of tobacco < NT < NT in the rural area plus urban sewage. A highly positive correlation was observed between different phosphorus fractions (especially the labile phosphorus), as well as different parameters of sorption/desorption, and amounts of iron and aluminum in sediments. It was found the highest amount of labile phosphorus in sediments collected at the end of winter and beginning of spring, particularly in the areas where tobacco is cultivated under CT.